A DISCOURSE ON LEAN CONSTRUCTION IN AFRICA, USING A SUPPLY CHAIN EXAMPLE - Fidelise EMUZE (Journal of Construction Project Management and Innovation)
discourse is defined as a unit of speech or writing longer than a sentence. It is about knowledge and its construction within a group or domain. A discourse therefore tends to focus on how a particular phenomenon is represented within a social group. This special issue on lean construction in Africa (LCiA) is an attempt to highlight how the knowledge and practice of lean construction is understood by researchers in the region. This opening article opens the discourse with why implementation of lean supply chains should be encouraged in a sector where projects are delivered by multiple parties with different interests. The differences in project interests require application of supply chain management and lean principles to avert well-known construction problems. The subsequent articles in this special issue motivate for the use of lean construction concepts, and tools by practitioners in the region.